2017
DOI: 10.1002/cptc.201700012
|View full text |Cite
|
Sign up to set email alerts
|

Vectorization and Intracellular Distribution of a Two‐Photon‐Absorbing, Near‐Infrared‐Emitting π‐Extended Boranil Dye

Abstract: A π‐extended boranil (PEB) dye has been synthesized and its photophysical properties have been recorded in a range of solvents. The dye exhibits an intense solvatochromic fluorescence emission covering the entire visible spectrum and the near infra‐red (NIR) region (from λ=534 to 764 nm) with quantum yields up to 69 %. Embedment of the PEB dye in the amphiphilic block copolymer Cremophor EL® leads to a strong emission (λem=617 nm, Φ=0.33) in PBS buffer. Moreover, two‐photon absorption (TPA) spectroscopy eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 39 publications
(20 reference statements)
0
23
1
Order By: Relevance
“…This is plausibly due to the minimal two-photon absorption by the key biomolecules when they are excited around 900 nm. 18 Through autofluorescence analysis, it is concluded that autofluorescence interference is minimal when the images are obtained under excitation at around 900 nm and, above all, when emission is collected from the red emission channel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is plausibly due to the minimal two-photon absorption by the key biomolecules when they are excited around 900 nm. 18 Through autofluorescence analysis, it is concluded that autofluorescence interference is minimal when the images are obtained under excitation at around 900 nm and, above all, when emission is collected from the red emission channel.…”
Section: Resultsmentioning
confidence: 99%
“…However, currently available fluorophores that satisfy the criteria are rare (Table S5 in the ESI † ). 18 …”
Section: Introductionmentioning
confidence: 99%
“…Four-coordinate organoboron chelates [1][2][3] are attractive targets for the design of photostable fluorescent dyes for the most varied applications,i ncluding bioimaging, [4][5][6][7][8][9][10][11][12] sensing, [13][14][15][16][17] and organic light-emitting diodes. [18] Much effort has been dedicated to the development of synthetically flexible platforms which enablet he photophysical fine-tuning of the dyes.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, three‐coordinate organoboron dyes have been also employed for bioimaging . Four‐coordinate organoboron dyes with chelate ligands, containing N‐ and/or O‐donor atoms, are of elevated interest for the development of optoelectronic devices, such as organic light emitting diodes, as photoaddressable materials, and very frequently as dyes for bioimaging and sensing …”
Section: Introductionmentioning
confidence: 99%